Measuring types and timing of childhood maltreatment: The psychometric properties of the KERF-40+ - Seitz, Katja I.; Gerhardt, Sarah; Schroeder, Claudius von; Panizza, Angelika; Thekkumthala, Dorothea; Bertsch, Katja; Herpertz, Sabine; Schmahl, Christian; Schalinski, Inga (PLOS ONE, 2022)
Childhood maltreatment, specifically during sensitive developmental periods, is a major risk factor for poor physical and mental health. Despite its enormous clinical relevance, there is still a lack of scales measuring different types, timing, and duration of childhood maltreatment. The current study sought to validate and determine the psychometric properties of the brief German version of the Maltreatment and Abuse Chronology of Exposure (MACE) scale, the KERF-40. The KERF-40 was administered as an interview (i.e., KERF-40-I) to 287 adult participants with and without mental disorders. Based on item response theory, items of the KERF-40-I were assigned to different types of maltreatment, resulting in a scaled version, the KERF-40+. Test-retest reliability was assessed in a small subsample (n = 14). Convergent and relative predictive validity were measured with correlations of the KERF-40+ and the Childhood Trauma Questionnaire (CTQ) as well as self-report measures of general and trauma-related psychopathology. Rasch analysis and fit statistics yielded a 49-item version, encompassing ten different types of maltreatment. The test-retest reliability of the KERF-40+ was shown to be acceptable to excellent for almost all global and subscale scores (.74 ≤ ρ ≤ 1.00), with the exception of the subscale emotional neglect (ρ = .55). Convergent validity with the CTQ was confirmed for both KERF-40+ global scores (.72 ≤ r ≤ .87) and corresponding subscale scores (.56 ≤ r ≤ .78). Relative predictive validity was reflected by significant small-to-moderate correlations between KERF-40+ global scores and indices of general and trauma-related psychopathology (.24 ≤ r ≤ .45). Taken together, the KERF-40+ appears to be suited for clinicians and researchers interested in retrospectively assessing different types, timing, and duration of childhood maltreatment experiences during sensitive periods in adults.